The effect of different agroecological zones and plant age on the cyanogenic potential of six cassava clones - Githunguri, C.M.; Ekanayake, I.J.; Chweya, J.A.; Dixon, Alfred G.O.; Imungi, J. (1998)
The effects of plant age on the cyanogenic potential (CNP) of leaves (CNP-L) and storage roots (CNP-R) of selected cassava clones, TMS 30001, TMS 4(2)1425, TME1, TME2,Isunikankiyanand Dakata Wariya were studied in two agroecological zones in West Africa. The two zones were represented by Kano in the Sudan Savanna zone with a unimodal annual rainfall averaging 844 mm and Ibadan in the forest-savanna transition zone with a bimodal rainfall averaging 1253mm per year. Plants were sampled periodically throughout the growing period. Highly significant correlation coefficients were obtained between CNP-L and CNP-R implying that CNP-R could be predicted from CNP-L, thus destructive sampling may not be necessary for determining CNP-R. Both CNP-L and CNP-R were much higher in Kano than in Ibadan at all sampling times. These results indicate that CNP was greater in the drier ecozone and suggests that both plant age and location were influencing the CNP of cassava roots and leaves. At both Kano and Ibadan, cassava CNP-R was lowest in cultivar TME1 and highest in TMS 50395. I leaves, CNP-L was highest in TMS 50395 and lowest in Isunikankiyan.